Dampak Sengketa Keluarga terhadap Pendidikan Anak: Mediasi Sebagai Alternatif Solusi - Muhammad Isnaini; Hery Kiswanto (Jurnal Kajian Gender dan Anak, 2026)
This study aims to analyze the impact of family resolution on children's education and examine the role of mediation as an alternative conflict resolution that is oriented towards protecting children's educational rights from an Islamic legal perspective. The study uses a qualitative approach with library research. Data were obtained from the Qur'an, tafsir books, laws and regulations, books, and scientific articles, and then analyzed using content analysis techniques through reduction, classification, interpretation, and conclusion drawing. The results show that family disputes have an impact on decreasing children's motivation and academic achievement, reduced parental attention, psychological and emotional disorders, and changes in social behavior that hinder the continuation of children's education. The study also found that mediation has a strong normative basis in Islamic law and positive Indonesian law, so it functions not only as a dispute resolution mechanism but also as an instrument for protecting children's educational rights by prioritizing the principle of the child's best interests. The integration of the concept of mediation, the principles of Alternative Dispute Resolution (ADR), and the values of Islamic family law strengthens mediation's position as an approach that can maintain continuity in child care and education despite family conflict. The implications of this research emphasize the importance of strengthening mediation practices oriented towards protecting children's educational rights and of developing an Islamic family mediation model that collaboratively involves mediators, judges, counselors, and educational institutions.